Transcriptional effects of copy number alterations in a large set of human cancers - Arkajyoti Bhattacharya (Nature Portfolio, 2020)
Copy number alterations (CNAs) can drive tumor progression in cancer by altering gene expression levels, but transcriptional adaption can skew CNA impact. Here, the authors present transcriptional adaptation to CNA (TACNA) profiling; a tool to extract the transcriptional effect of CNAs from expression data without requiring paired CNA profiles.